Association of plasma endocan levels with metabolic parameters and predictive value of endocan for the development of complications in patients with type 2 diabetes mellitus: An observational study - Kenana Ljuca; Mensura Aščerić; Olivera Batić-Mujanović; Svjetlana Loga-Zec; Nadina Ljuca; Emir Bećirović; Samir Bejić; Predrag Jovanović; Minela Bećirović (Biomolecules & Biomedicine)
The aim of the current research was to investigate the association between plasma endocan levels and metabolic control parameters, as well as to evaluate its predictive value for clinical complications in patients with type 2 diabetes mellitus (DMT2). A total of 100 DMT2 patients participated in this prospective observational study. Plasma endocan levels were significantly elevated in DMT2 patients with HbA1c>7% (1.38±0.33 vs. 0.68±0.23 ng/mL; p<0.0001), compared to patients with HbA1c ≤7%. Patients with plasma endocan concentrations >1.10 ng/mL (median value of 1.10 ng/mL) demonstrated significantly higher levels of metabolic parameters: body mass index (BMI), HbA1c%, fasting glucose level, LDL cholesterol, total cholesterol, triglycerides, along with significantly lower HDL cholesterol levels. Furthermore, patients with plasma endocan levels >1.10 ng/mL were found to have an increased risk for the following complications: retinopathy (RR: 2.7500; 95% CI: 1.2150 to 6.2244; p= 0.0152, nephropathy (RR: 2.0952; 95% CI: 1.2294 to 3.5710; p=0.0065), neuropathy (RR: 1.9945; 95% CI: 1.2025 to 3.3081); p=0.0075 ), angina pectoris (RR: 2.4881; 95% CI 1.0865 to 5.6979; p=0.0311, hypertension (RR: 1.1372; 95% CI 1.0060 to 1.2856; p=0.0398), cardiomyopathy (RR: 2.6190; 95% CI 1.1507 to 5.9612; p=0.0218), myocardial infarction (RR: 9.4286; 95% CI 1.2742 to 69.7697; p=0.0280) and stroke (RR: 4.4638; 95% CI 1.3765 to 14.4758; p=0.0127). Correlation analysis revealed that plasma endocan levels were positively correlated with HbA1c% (r=0.856, p<0.0001), fasting glucose level (r=0.631, p<0.0001), LDL (r=0.347, p=0.0004), cholesterol (r=0.282, p=0.0045) and triglycerides (r=0.366, p=0.0002). Conversely, plasma endocan levels were negatively correlated with HDL cholesterol (r= - 0.429, p<0.0001). In conclusion, higher plasma endocan levels were strongly associated with poor metabolic control in DMT2 patients and exhibited significant predictive value for both microvascular and macrovascular complications.